Comparative evaluation of the entrepreneurial profile by gender in university students of business management engineering - Arturo, González Torres; Hernández, María Luisa Pereira; Echeagaray, Melissa Edith Salazar (Edelweiss Applied Science and Technology, 2025)
Mexico has stood out in the last decade for its significant entrepreneurial activity, as the rate of creation of new small and medium-sized enterprises has increased considerably. In this context, the involvement of educational institutions is a cross-cutting issue aimed at providing a broader understanding of the various factors influencing this phenomenon. The objective of this study is to evaluate gender differences in the entrepreneurial traits of students enrolled in the Business Management Engineering program at the Instituto Tecnológico de Milpa Alta. A descriptive, observational, comparative, and cross-sectional research design was employed, utilizing the questionnaire developed by the Spanish company CIMO, which has a Cronbach’s Alpha reliability index of 0.93. The study involved 45 students, and Student’s t-test was used to compare mean traits and identify significant gender differences. No statistically significant differences were observed between the entrepreneurial profiles of men and women. Men achieved a mean score of 70.15 points, while women scored 64.81 points. Both groups exceeded the 60-point threshold established by CIMO as an indicator of an adequate entrepreneurial profile. The findings suggest that entrepreneurship among university students is not determined by gender but by individual, educational, and attitudinal factors. Both genders demonstrated a competent entrepreneurial profile, indicating that the entrepreneurial competencies of the program are developing effectively.